(untitled) - Alan G Sharpe (London, 1991)
The book provides introduction to new and exciting areas of research such as cluster compounds, bioionrganic chemistry, organometallic chemistry, magnetic and electronic properties, and inorganic spectroscopy. It provides a detailed explanation of the relevance of thermodynamics, structures and kinetics to the science, and highlights both the successes and limitations of theories of inorganic chemistry
Keywords: chemistry, inorganic